Visualization of sub-nanometer scale multi-orientational ordering in thin films of polymer/non-fullerene acceptor blends. Issue 46 (18th November 2022) - Bothra, Urvashi; Hui, Pramiti; Tan, Wen Liang; Gann, Eliot; Venugopal, Hariprasad; Subramaniam, Chandramouli; Liu, Amelia C. Y.; McNeill, Christopher R.; Kabra, Dinesh
Abstract : A range of advanced imaging techniques are employed to study the micron- and nano-scale morphology of a polymer/non-fullerene acceptor blend. Cryo-electron microscopy in particular reveals nanoscale variations in molecular orientation and order. Abstract : Improvement in the efficiency of organic photovoltaics (OPVs) is mainly attributed to non-fullerene acceptors (NFAs). However, NFAs exhibit an anisotropic chemical structure, resulting in over-sized aggregation, which can affect the exciton dissociation and charge transport. While the effect of different morphologies on the device performance has been observed in several studies, little is known about the composition and local molecular ordering in bulk heterojunction (BHJ) blend films of the polymer donor and NFAs. Here, we manipulate the morphology of blend films from large micron-sized phase-separated domains to fine-scale nano-domains via varying the drying kinetics of the film formation. We investigate the composition by micro-Raman spectroscopic studies of these blend films and visualize the molecular ordering at the sub-nanometer scale using a combination of cryo-electron microscopy and X-ray studies. Interestingly, we find that the molecules are oriented differently at the edge and at the center of these domains, a feature that has not been observed previously in spin-coated films containing NFAs. Moreover, we have extended our study to other donor-NFA systems and have observed a similar effect of drying kinetics on the microstructural and optical properties. Furthermore, our study shows that the change in the performance of the PTB7-Th :IEICO-4F device due to micron- and nano-sized morphology is relatively less, which is in contrast to a general notion of OPV systems.